1996
DOI: 10.1111/j.1476-5381.1996.tb15334.x
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A2 receptor‐induced inhibition of leukotriene B4 synthesis in whole blood ex vivo

Abstract: Engagement of adenosine A2 receptors suppresses several leukocyte functions. In the present study, we examined the effect of adenosine on the inhibition of leukotriene B4 (LTB4) synthesis in heparinized human whole blood, pretreated with lipopolysaccharide (LPS) and tumour necrosis factor α (TNF‐α) and stimulated with the chemotactic peptide, N‐formyl‐Met‐Leu‐Phe (FMLP). The FMLP‐induced synthesis of LTB4 in whole blood pretreated with LPS and TNF‐α was dose‐dependently inhibited by adenosine analogues in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 47 publications
(46 reference statements)
2
39
0
Order By: Relevance
“…The non-selective PDE inhibitors and the PDE III-selective inhibitors were not potent against either mediator and the PDE V-selective inhibitors were not active. The activity observed with dipyridamole was probably due to its inhibition on adenosine uptake by red blood cells rather than its inhibition of PDE V (Krump et al, 1996;. The 5-LO inhibitor L-739,010 had no e ect on TNF-a but was very potent against LTB 4 .…”
Section: E Ect Of Double Lps Pre-incubations and Fmlp Stimulation On mentioning
confidence: 92%
“…The non-selective PDE inhibitors and the PDE III-selective inhibitors were not potent against either mediator and the PDE V-selective inhibitors were not active. The activity observed with dipyridamole was probably due to its inhibition on adenosine uptake by red blood cells rather than its inhibition of PDE V (Krump et al, 1996;. The 5-LO inhibitor L-739,010 had no e ect on TNF-a but was very potent against LTB 4 .…”
Section: E Ect Of Double Lps Pre-incubations and Fmlp Stimulation On mentioning
confidence: 92%
“…A [46,77,79]. It has been shown that adenosine is an inhibitor of transcellular metabolism of LTA 4 , released by leucocytes upon activation with physiological agonists [79]. The relative role of transcellular metabolism in the formation of LTC 4 in asthma and other pathophysiological conditions remains to be clarified.…”
Section: Cellular Formation Of Leukotrienesmentioning
confidence: 99%
“…Several lines of evidence suggest that stimulated leucocytes can release arachidonic acid or LTA 4 , which can be further metabolized by other surrounding cells (so-called transcellular metabolism) [74][75][76][77][78]. A [46,77,79]. It has been shown that adenosine is an inhibitor of transcellular metabolism of LTA 4 , released by leucocytes upon activation with physiological agonists [79].…”
Section: Cellular Formation Of Leukotrienesmentioning
confidence: 99%
“…At therapeutic range (5 to 15 g/mL), caffeine blocks A 1 and A 2a adenosine receptors (ARs) stimulating ventilation (2-4). Recently, caffeine has also been linked to a decrease in the incidence of bronchopulmonary dysplasia and cerebral palsy in extremely premature infants (5,6), although the mechanisms explaining these findings have not been elucidated.The natural ligand for ARs, adenosine, has a crucial role in multiple biologic processes including inflammation (7,8). The increase in tumor necrosis factor-alpha (TNF-␣) release by adult peripheral blood monocytes (PBM) in response to lipopolysaccharide (LPS) exposure can be abolished by pretreatment with A 2a R agonists (9,10).…”
mentioning
confidence: 99%
“…The natural ligand for ARs, adenosine, has a crucial role in multiple biologic processes including inflammation (7,8). The increase in tumor necrosis factor-alpha (TNF-␣) release by adult peripheral blood monocytes (PBM) in response to lipopolysaccharide (LPS) exposure can be abolished by pretreatment with A 2a R agonists (9,10).…”
mentioning
confidence: 99%